Scleral and choroidal thickness in secondary high axial myopia - Shen, Ling; Jonas, Jost B. (Retina, 2016)
Purpose: To assess differences in scleral and choroidal thickness between eyes with secondary high axial myopia caused by congenital glaucoma, eyes with primary high axial myopia, and nonhighly myopic eyes. Methods: The study consisted of 301 Chinese individuals with a mean age of 23.9 ± 22.6 years and mean axial length of 24.8 ± 4.2 mm. It included the “secondary highly myopic group” (SHMG) because of congenital glaucoma (n = 20 eyes; axial length >26.0 mm), the “primary highly myopic group” (PHMG) (n = 73; axial length >26.0 mm), and the remaining nonhighly myopic group (NHMG). Results: The secondary highly myopic group versus the primary highly myopic group had significantly thinner sclera in the pars plana region (343 ± 71 μm versus 398 ± 83 μm; P = 0.006), whereas scleral thickness in other regions did not differ significantly between both highly myopic groups and was significantly thinner in both highly myopic groups than in the NHMG. Mean total scleral volume did not differ significantly (P > 0.20) between any group (SHMG: 659 ± 106 μm3; PHMG: 667 ± 128 μm3; NHMG: 626 ± 135 μm3). Choroidal thickness was significantly thinner in both highly myopic groups than in the NHMG, with no significant differences between both highly myopic groups. Choroidal volume did not differ significantly (P > 0.40) between any of the groups (SHMG: 43 ± 12 μm3; PHMG: 43 ± 13 μm3; NHMG: 46 ± 17 μm3). Conclusion: In secondary high axial myopia, the sclera gets thinner anterior and posterior to the equator; whereas in primary high axial myopia, scleral thinning is predominantly found posterior to the equator. Because volume of sclera and choroid did not differ between any group, scleral and choroidal thinning in myopia may be due to a rearrangement of tissue and not due to the new formation of tissue.